Total Synthesis of Obolactone via Regioselective Carbonyl Desaturation - Drury, Paige A.; Sullivan, Ciara L.; Pottle, Haley L.; Quinn, Kevin J. (Synlett, 2025)
Total synthesis of the dihydro-γ-pyrone natural product (±)-obolactone is reported. The synthesis relies on the development of a strategy for regioselective carbonyl desaturation of tetrahydropyranone precursors via site-selective C–H bond oxidation. Identification of suitable oxidants for this transformation in a model system as well as implementation in a one-pot procedure that provides direct access to regiochemically defined dihydro-γ-pyrones from readily accessible tetrahydropyranols are described. Using this approach, obolactone was prepared in a single step from the originally proposed structure of cryptoconcatone H and just four steps from C2-symmetric (±)-1,8-nonadiene-4,6-diol in 24% overall yield.
Keywords: Obolactone; Total synthesis; Dihydro-γ-pyrone; C–H bond oxidation; Carbonyl desaturation; Regioselectivity